Space Law: Second Edition - Hobe, Stephan, LL.M. (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Space tourism, satellite use, military scope or extra-terrestrial resource extraction: space law is increasingly shaping national and international interests. In clear diction and with illustrations and supporting graphics, Hobe presents all relevant legal aspects of space use on the basis of international space law and all relevant national space legislations. Focus on new developments The 2nd edition takes into account the new legal problems resulting from the rapidly advancing conquest of space. This concerns previously unknown areas, in particular: Space travel by private companies NASA's Artemis programme Concrete considerations for the colonisation of the Moon and Mars Resource extraction on celestial objects Traffic rules for outer space.